The Impact of Industrial Effluent Discharge on the Physicochemical Characteristics of Agricultural Soil - Ifeoma, Oronsaye; Emmanuel, Maduagwu Chinonso (Darul Yasin Al Sys, 2025)
This study investigates the effect of agricultural industrial effluent discharge on soil and crops. Soil and crop samples from agricultural fields irrigated with industrial effluent were collected between August 2024 and January 2025. The samples were analysed for heavy metals, including Zinc, Copper, Iron, Lead, Manganese, Cadmium, and Chromium, using standard analytical methods. Data were processed using simple descriptive statistics with Microsoft Excel. Results indicated that Zinc concentrations in crops from Farms 3 to 5 ranged from 0.08 to 0.3 mg/kg, within the WHO/FAO safe limit of 0.60 mg/kg. However, crop samples from Farms 1 and 2 exceeded the WHO/FAO permissible Zinc limit. The concentrations of Copper, Zinc, Iron, and Cadmium in the crops were generally within the WHO permissible levels. The accumulation of heavy metals in crops followed the order: Potatoes, Guinea corn, Garden Egg, Maize and Okra. The findings suggest that the consumption of crops from Farms 1 and 2 could pose significant health risks. The study recommends treating industrial effluent before discharge to mitigate potential health hazards.